Proton Exchange Membrane with Dual‐Active‐Center Surpasses the Conventional Temperature Limitations of Fuel Cells - Yucong Liao; Shengqiu Zhao; Rui wang; Junjie Zhang; Hao Li; Bingxuan Liu; Yao Li; Aojie Zhang; Tian Tian; Haolin Tang (Advanced Science)
Abstract High temperature‐proton exchange membrane fuel cells (HT‐PEMFC) call for ionomers with low humidity dependence and elevated‐temperature resistance. Traditional perfluorosulfonic acid (PFSA) ionomers encounter challenges in meeting these stringent requirements. Herein, this study reports a perfluoroimide multi‐acid (PFMA) ionomer with dual active centers achieved through the incorporation of sulfonimide and phosphonic acid groups into the side chain. The fluorocarbon skeleton and multi‐acid side chain structure facilitate the segregation of hydrophilic and hydrophobic microphases, augmenting the short‐range ordering of hydrophilic nanodomains. Furthermore, the introduction of a rigid segment‐benzene ring is employed to decrease side chain flexibility and raise the glass transition temperature. Notably, the prepared membrane exhibits a conductivity of 41 mS cm−1 at 40% relative humidity, showcasing a 1.8 times improvement over that of PFSA. Additionally, the power output of the H2‐air fuel cell based on this membrane reaches 1.5 W cm−2 at 105 °C, marking a substantial 2.3 times enhancement compared to the PFSA. This work demonstrates the unique advantages of perfluorinated ionomers with multiple protogenic groups in the development of high‐performance high‐temperature electrolyte materials.